2002
DOI: 10.1007/s00442-002-0872-1
|View full text |Cite
|
Sign up to set email alerts
|

Light gradient partitioning by tropical tree seedlings in the absence of canopy gaps

Abstract: To explore the importance of light availability for seedling growth in low light environments, we examined light-dependent growth, biomass allocation and mortality of tree seedlings growing in sites with 0.2-6.5% full sun, the range of light commonly encountered in the understory of closed canopy, lowland tropical forests. We transplanted seedlings of the canopy tree species, Dipteryx panamensis, Virola koschnyii, and Brosimum alicastrum into second-growth forest and native tree plantations at La Selva Biologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
235
6
17

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(271 citation statements)
references
References 49 publications
13
235
6
17
Order By: Relevance
“…The results we obtained for canopy discontinuity are considered intermediate in relation to the 9.0-26.0% reported for other semideciduous forests or even the 0.2-6.0% reported for evergreen forests (Martins & Rodrigues 2002;Montgomery & Chazdon 2002;van den Berg & Santos 2003;Meira Neto et al 2005). Although canopy discontinuity showed no correlation with individuals already established, it must certainly contribute to the distribution of regenerating individuals, as must other factors, such as the availability of water and nutrients.…”
Section: Relationships Between Species and Spatial-environmental Varimentioning
confidence: 81%
“…The results we obtained for canopy discontinuity are considered intermediate in relation to the 9.0-26.0% reported for other semideciduous forests or even the 0.2-6.0% reported for evergreen forests (Martins & Rodrigues 2002;Montgomery & Chazdon 2002;van den Berg & Santos 2003;Meira Neto et al 2005). Although canopy discontinuity showed no correlation with individuals already established, it must certainly contribute to the distribution of regenerating individuals, as must other factors, such as the availability of water and nutrients.…”
Section: Relationships Between Species and Spatial-environmental Varimentioning
confidence: 81%
“…Many authors showed that light availability in the under storey can be limiting for plants. For example, low available light in the understorey can reduce survival probability of some tree seedlings (Montgomery and Chazdon 2002). On the other hand, some understorey plants can efficiently use the small light quantities that reach the forest floor (Chazdon et al 1996).…”
Section: Trichomanes Pinnatuw Adiantuitr Nti/ltisorvm Schizaea Fluminmentioning
confidence: 99%
“…Studies on tropical forests demonstrated that light conditions on the forest floor play an important role in the growth and survival of seedlings (Montgomery and Chazdon, 2002), species diversity (Schnitzer and Carson, 2001) and on seedling abundance and distribution (Nicotra et al, 1999). In situ studies on seedling growth and survival in Cerrado species are scarce.…”
Section: Discussionmentioning
confidence: 99%